The teaching of the processes of science using an experiment in radiation biology - Jacalne, Lucita Gutierrez 1940- (s.n.], 1974)
This study determined the effects of gamma radiation on bush sitao seeds. Specifically, this work investigated the following: (1) seed germination; (2) plant survival; (3) plant height at the start of flowering; (4) number of leaves; (5) seed yield; (6) seed fertility; (7) seed viability; and (8) some gross morphological abnormalities that have occurred in irradiated bush sitao plants.